Manpower requirements for management and professional personnel - Tillman, Frank A., 1937- (FT Press, 2012)
It is notoriously difficult to measure work in management, professional, and service roles, where management can't quantify the number of units produced, and repetition of work occurs only on much longer cycle times. Nevertheless, you must make accurate measurements to correctly size your organization--and current economic uncertainty makes this even more critical. In Manpower Requirements for Management and Professional Personnel, Frank A. Tillman and Deandra T. Cassone present an exceptionally accurate analytical approach to assessing manpower requirements throughout white-collar environments, helping companies systematically, carefully select individuals who are best suited for a wide variety of roles throughout the business. Tillman and Cassone's structured, statistical staffing model accounts for tasks, the time it takes to perform them, and the inevitable significant variability in task times. Reflecting the types of jobs it seeks to quantify, it takes a broader view of what constitutes a "task" or "work unit," enabling decision-makers to utilize already available data in powerful new ways. Tillman and Cassone detail data sources, functions, activities, workload drivers, inflows, processing, outflows, and more. They also address complex issues such as skill-mix trade-offs that any staffing model for managers and professionals needs to handle. Tillman and Cassone's model can be used as a management tool for analyzing, determining, and redistributing staffing resources throughout the organization and for both future resource planning and "what-if" analysis.